The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1136/bjo.2008.156356
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain fatty acids, increased in tears of blepharitis patients, are not toxic for conjunctival cells

Abstract: The increase in BCFAs in the tears of blepharitis patients does not consistently participate in the conjunctival cell changes throughout the course of the disease. Instead, it is likely an adaptive response of the ocular surface to the lack of tears, possibly increasing meibum fluidity, thus enhancing lacrimal film stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
0
22
2
1
Order By: Relevance
“…Other groups of abnormal meibum such as seborrheic alone or seborrheic with meibomian seborrhea did not show a significant difference in the fatty acid chain composition of meibum compared with normal. 10 These results are contrary to those of Joffre et al 47 who showed a 60% decrease in saturated fatty acids and a 50% increase in hydrocarbon chain branching in meibum from MGD. Such large changes are well above the detection limit of infrared spectroscopy and yet, we did not observe them.…”
Section: Gn Foulks and D Borchmancontrasting
confidence: 85%
See 1 more Smart Citation
“…Other groups of abnormal meibum such as seborrheic alone or seborrheic with meibomian seborrhea did not show a significant difference in the fatty acid chain composition of meibum compared with normal. 10 These results are contrary to those of Joffre et al 47 who showed a 60% decrease in saturated fatty acids and a 50% increase in hydrocarbon chain branching in meibum from MGD. Such large changes are well above the detection limit of infrared spectroscopy and yet, we did not observe them.…”
Section: Gn Foulks and D Borchmancontrasting
confidence: 85%
“…Shine and McCulley 10 have shown that meibum from donors with meibomian keratoconjunctivitis contains waxes and cholesterol esters and triglycerides 45 that are more saturated and contain less monounsaturated hydrocarbons 46 and branched hydrocarbon chains compared with meibum from normal donors. In contrast, Joffre et al 47 have shown that meibum from donors with MGD contains less saturation and more branching. Meibomian gland dysfunction meibum also contains higher levels of phosphatidylcholine, 48 phospholipid unsaturation, 49 wax esters, 25 and lower levels of phosphatidylethanolamine, sphingo- …”
Section: Changes In Meibum With Meibomian Gland Dysfunctionmentioning
confidence: 91%
“…Infrared studies have shown that lipid order and phase transition temperatures are higher in meibum of donors with meibomian gland disease. 44 Recently, Joffre et al 74 demonstrated that the fatty acid profile of the excreta collected by Schirmer test strips in people with blepharitis is significantly different from controls. Total saturated fatty acids were 9.3% in those with blepharitis versus 24.6% in controls, with lower quantities of palmitic (C 16:0 ) and stearic (C 18:0 ) acids.…”
Section: Meibum Lipid Changes In Diseasementioning
confidence: 98%
“…Only the mitochondrial dehydrogenase activity was significantly decreased in relation to the isoC 20 concentration increase. 74 Ocular rosacea has been associated with MGD. 97 The concentration of triglycerides and FFA, especially the mono-and polyunsaturated forms, is increased and may be responsible for the activation of neutrophils and inflammatory mediators.…”
Section: Meibum Lipid Changes In Diseasementioning
confidence: 99%
See 1 more Smart Citation